Miradas de la Transición. La fotografía de Enrique Cano [ 1975 - 1990 ] - Marcos Molano, Mar (EDITUM. Ediciones de la Universidad de Murcia, 2025)
"Looks from the transition, the photograph of Enrique Cano (1975-1990)", is a tour of the most personal work of Madrid's photographer, a series of snapshots indispensable to understand the historical and political moment they portray. The photographs make a cartography of the city of Madrid touring their most intimate corners, populated with characters to which they invite their stories to their camera. Each of these stories becomes, in the whole of his work, in the history of an entire country, that Spain that travels towards freedom in the period known as transition.